COMPARING OF EMOTIONAL WORDS IN THE FORMATION OF EXPRESSIONS IN ENGLISH AND UZBEK LANGUAGES - Hayitboyeva Oltinoy Shonazar qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article focuses on the comparison of emotional words in two different languages: Uzbek and English. Monitoring the replenishment of the Uzbek and English phraseological fund is crucial because idioms are constantly emerging as a result of scientific advancements, the adoption of new technologies, political games, and military conflicts—all of which have a significant impact on the English and Uzbek people.